Cultivating Spiritual Intelligence in Education during the Era of Artificial Intelligence Based on the Concept of Educational Psychology in the Al-Qur'an - Ni'am, Ahmad Miftahun; Parhan, Parhan; Basyarahil, Ibrahim; Hidayaturrohmah, Nur (Jurnal Penelitian Ilmu Ushuluddin, 2025)
This research aims to analyze the relationship between spiritual intelligence and artificial intelligence from the perspective of Al-Qur'an. Its primary objectives include identifying the limitations of artificial intelligence in replicating human intelligence, exploring the concept of human intelligence according to Al-Qur'an, highlighting the superiority of spiritual intelligence, and offering Qur'anic guidance on balancing spiritual intelligence and artificial intelligence. The study employs a qualitative method with a literature review approach. Relevant literature sources are analyzed to provide a comprehensive understanding of the topic. The findings conclude that artificial intelligence has inherent limitations in replicating human emotional and spiritual aspects. Al-Qur'an emphasizes the importance of balancing spiritual intelligence and technological advancements to ensure that humanity does not become overly absorbed in technological progress, neglecting the essential aspects of life vertically (relationship with God) and horizontally (relationship with others). For future research, it is recommended to conduct empirical studies that observe how the integration of spiritual intelligence in managing technology, particularly artificial intelligence, can support the development of ethical and human-centered technologies.